Aplikasi Penggabungan Warna Menggunakan RGB dan CMYK Berbasis Desktop - Rezky Fahmi; Irmayani Pawelloi; Wahyuddin Wahyuddin; Ahmad Selao; Ade Hastuty (Jurnal Sains dan Ilmu Terapan, 2025)
The use of digital technology for visual and interactive color mixing, particularly on desktop platforms, is still not optimal. This research aims to design and develop a desktop application that can mix colors from the RGB and CMYK systems in real-time. The research method used is experimental and applicative, with a scope that includes literature study (library research) and field data collection (field research). The application design is carried out through the integration of color palettes and sliders as input media, followed by a color conversion process between CMYK and RGB to calculate the average value. The test results show that this application is capable of performing the color mixing process responsively and accurately, according to the visual input provided. This application has the potential to be used as a medium for color education, visual experiments, and as a tool for developing creativity in digital art, which is highly beneficial for students, professionals, and the creative industry in the fields of graphic design and animation,